The Beta Amyloid Dysfunction (BAD) Hypothesis for Alzheimer’s Disease - Hillen, Heinz (Frontiers in Neuroscience, 2019)
Beta amyloid, Aβ 1-42, originally named as Amyloid A4 protein is one of the most investigated peptides in Neuroscience and has attracted substantial interest since its discovery as the main insoluble fibril type protein in cerebrovascular plaques (Glenner and Wong, 1984, Masters et al.,1985) of Alzheimer`s Disease (AD). Since its discovery, Aβ was regarded per se as a „bad molecule“ from the very beginning, triggering the so called „beta amyloid cascade hypothesis“ (Hardy and Higgins, 1992). This hypothesis ignored any physiological function for steadily generated Aß monomer with normal production and turnover rate (Bateman, R., 2006). Accordingly, pan-Aβ related therapeutic approaches were designed to eliminate or lower all three structural isoforms in parallel: 1. the pre-amyloid monomer, 2. the misfolded oligomer and 3. the final fibril. While we already knew about poor correlations between plaques and cognitive decline quite early (Terry et al., 1991), more importantly, also data for an essential benign physiological role for Aβ monomer at low concentrations were surprisingly not considered to be relevant. Here I describe a different Beta Amyloid Hypothesis, the so called „Beta Amyloid Dysfunction Hypothesis“, which in contrast to the „Beta Amyloid Cascade Hypothesis“ builds on an important physiological role of nascent Aβ monomer in accelerated synaptic trafficking in the vesicle budding process. Disease relevant early Aß pathology starts when the control of the folding process is disturbed leading then to misfolded Aß oligomers. These early species compete with the physiological Aβ monomer and exert their neurotoxicity through promiscuous receptors for sticky oligomer type Aß aggregates. The Beta Amyloid Dysfunction (BAD) Hypothesis is introduced and shown to explain negative clinical results of Gamma secretase - and BACE inhibitors as well as pan-Aβ isotype unselective immunotherapies. This new hypothesis also gives clear guidance to what really needs to be done therapeutically to bring this genetically validated target back into successful clinical testing in Alzheimer`s disease. The BAD hypothesis will need further refinement in particular through more detailed exploration for the role of physiological Aβ monomer.